State, violence, and legitimacy in India - Khanikar, Santana (New Delhi, India : Oxford University Press, 2018)
Study conducted in Delhi and Lakhipathar village of Tinsukia District, Assam, India.
Includes bibliographical references (pages 251-262) and index.
Also issued online.
Keywords: United Liberation Front of Assam; India. -- Army; Police misconduct -- India -- Delhi; Political violence -- India -- Delhi; Legitimacy of governments -- India -- Delhi; Legitimacy of governments -- India -- Lakhipathar; Abuse of administrative power -- India -- Lakhipathar; Lakhipathar (India) -- Politics and government